'Local governance' in policing: The trade-offs between performance, knowledge and risk management in balancing quality with quantitative measures. - Pilcher, Robyn; Collier, P.; Hodges, S.; Ward, C.; Mussell, N.; Van der Zahn, J-L. (Unknown, 2009)
In discussing policing issues the press, public and politicians routinely focus on quantitative measures as these are perceived to be easier to measure and understand. However, this often overshadows pivotal qualitative details of major police processes such as the initial investigation which can significantly influence investigative outcomes. This study aims to develop-test and evaluate a theoretical model of local governance (i.e. decisions at the local level) in which trade-offs take place between knowledge, risk and performance in decisions at different organisational levels. The research findings highlight opportunities that exist for developing a more holistic and balanced approach to performance evaluation in the public sector, by balancing quantitative measures with more qualitative indicators.